Making Sense of Digital Humanities - Chambliss, Julian; Moll, Ellen (Open textbook library., 2022)
Taking up the challenge of navigating the complex world of digital humanities, Making Sense of Digital Humanities offers readers an exploration of the many ways scholars have employed the diverse toolkit of digital humanities to create a better understanding of the synergies and disruptions created by technological change. Rooted in a concern for the daunting tasks associated with teaching and learning about the digital humanities, this volume hopes to provide easy entry into a complex topic while highlighting how an understanding of digital humanities can transform our thinking about technology in the modern world.